A Mixed Ligand Approach for the Asymmetric Hydrogenation of 2‐Substituted Pyridinium Salts. Issue 16 (12th July 2016) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract: Herein we describe a new methodology for the asymmetric hydrogenation (AH) of 2‐substituted pyridinium salts. An iridium catalyst based on a mixture of a chiral monodentate phosphoramidite and an achiral phosphine was shown to hydrogenate N ‐benzyl‐2‐arylpyiridinium bromides to the corresponding N ‐benzyl‐2‐arylpiperidines with full conversion and good enantioselectivity. The mechanism of the reaction under optimized conditions was investigated via kinetic measurements and isotopic labeling experiments. Our study suggests that the hydrogenation starts with a 1, 4‐hydride addition and that the enantiodiscriminating step involves the reduction of an iminium intermediate. Abstract :